Economic growth and valuation of the environment a debate - Ierland, E. van (Ekko van); Straaten, Jan van der.; Vollebergh, Herman R. J.; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar Pub., 2001)
The debate on the valuation of nature and the environment, sustainable national income and economic growth is one of prime importance in environmental economics. Economic Growth and Valuation of the Environment deals with the fundamental approaches to calculating sustainable national income and their implications for the valuation of the environment.
pt. 1. Setting the stage -- pt. 2. Reflections -- pt. 3. Green accounting and sustainable national income -- pt. 4. Conclusion.
Includes bibliographical references and index.
Keywords: Economic development -- Environmental aspects; Sustainable development -- Environmental aspects; Electronic books